METAPSIKOSIS TUHAN DALAM LOKALITAS KETUHANAN BALI : KAJIAN TEKS TUTUR GONG BESI - Harsananda, Hari; Wayan Gaduh, Acyutananda Wayan Gaduh (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2026)
This research explores the local Balinese theological dimensions contained in the Tutur Gong Besi text. Utilizing a qualitative approach with a hermeneutic framework, this study aims to identify the distinctive characteristics of Balinese Theology that differentiate it from normative or mainstream Hindu theology. The primary finding of this research is the concept of